SYNTHESIS OF Zn2SnO4 AS PHOTOCATALYST MATERIAL BY SONOCHEMISTRY METHOD - Hendayana, Rian
The usage of synthetic dyes in textile industries has been undeniable since it is relatively cheaper, long lifetime, and it has colors variety. Unfortunately this leads to the environmental problem since synthetic dyes produce harmful and non biodegradable wastes. Photodegradation by photocatalyst has become a promising method to handle dyes waste. Photodegradation has many advantages such as it is able to mineralize the organic compounds, no wastewater problem, and processing in mild pressure and temperature. This research aimed to synthesize Zn2SnO4 (ZTO). ZTO has potential in the photocatalytic application due to its high electron diffusivity, and favorable stability in acidic and basic environment. ZTO was succesfully synthesized by sonochemistry method at the optimum pH of 8.5 and calcined temperature at 1000 oC and 1200 oC for 6 hours. Volume fraction of ZTO 1000 and ZTO 1200 are 94.02% and 96.42%, respectively. SEM analysis indicated that particle size of ZTO 1000 and ZTO 1200 are 0.07 µm and 2.13 µm, respetively with each band gap of 3.7 eV and 3.44 eV. Photocatalitic activity was measured by observing degradation of 6 x 10-6 M methylene blue. The activity of 1 gram ZTO 1000 and ZTO 1200 are 89.52% and 84.02%, respectively under 180 minutes of UV irradiation. The different in activity for ZTO 1000 and ZTO 1200 was due to their particle size. ZTO 1000 was better than ZTO 1200 since it has smaller particle size hence it has larger surface area.